STUDY OF THE MAGNETIC FIELD OF AN SINGLE-PHASE INDUCTION MOTORS - Егоров, Алексей; Егорова, Ольга; Глебова, Марина (SWorldJournal, 2023)
Induction capacitor motors are widely used in electric drive systems of various industrial and domestic mechanisms. Every year the scope of use of these machines continues to expand, both in new areas of technology and as a replacement for more complex el